2011
DOI: 10.3329/jhpn.v29i5.8906
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Its Effects on Medical Students: A Cross-sectional Study at a College of Medicine in Saudi Arabia

Abstract: Medical education is perceived as being stressful, and a high level of stress may have a negative effect on cognitive functioning and learning of students in a medical school. This cross-sectional study was conducted to determine the prevalence of stress among medical students and to observe an association between the levels of stress and their academic performance, including the sources of their stress. All the medical students from year one to year five levels from the College of Medicine, King Saud Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
431
20
39

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(562 citation statements)
references
References 30 publications
72
431
20
39
Order By: Relevance
“…Similar findings were made in a number of other studies. 2,5,7,13,14 The students in our study enrolled in a problem-based learning curriculum which commenced in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were made in a number of other studies. 2,5,7,13,14 The students in our study enrolled in a problem-based learning curriculum which commenced in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…A formação médica parece ter um impacto negativo sobre a saúde mental dos alunos, podendo haver vários determinantes dessa situação, como a sobrecarga acadêmica (20)(21) , frequências elevadas de estresse (22)(23) , ansiedade e depressão (24)(25)(26) e relação destes com menores valores da qualidade de vida.…”
Section: Discussionunclassified
“…In many medical schools, the environment itself can cause significant pressure among medical students due to its authoritarian and rigid system which encourages competition rather than cooperation between learners. (4,5) The estimated prevalence of emotional disturbance found in different studies on medical students was higher than that in the general population. In a British study, the prevalence of stress among medical students was found to be 31.2% (6).…”
Section: Issn: 2320-5407mentioning
confidence: 98%